Is Anatomic Variation of Superficial Peroneal Nerve Having Medical Implication in Internal Fixation of Lateral Malleolus Fractures? A Case Report - G., Kastanis; E., Trachanatzi; P., Kapsetakis; E., Lazanaki; C., Chaniotakis; I., Stavrakakis; A., Pantouvaki (International Journal of Innovative Research in Medical Science, 2022)
Superficial peroneal nerve (SPN) is one of the terminal branches of the common peroneal nerve which innervates muscles of the lateral compartment of the leg. It is reported in literature in cadaveric studies, that there is anatomic variation of the SPN according to course and distribution and how important this finding is in many surgical interventions around leg, ankle, and foot, with scope to avoid iatrogenic damage of the respective nerve. The aim of this study is to present a woman of 67 years old who presented in emergency department after a fall with a bimalleolar fracture of the left ankle and paresthesia distribution of superficial peroneal nerve (dorsal surface of the foot, and 3rd to 5th toes) and based on this case to analyze if this anatomic variation of SPN has an essential role in lateral approach for internal fixation of lateral malleolar fractures.